Visco-elastic impacts on an unsteady MHD flow past a constant slanted plate in the presence of viscous dissipation, radiation and chemically reactive species: a numerical study (Journal of Naval Architecture and Marine Engineering, 2023)
A numerical investigation of a natural convection magnetohydrodynamics (MHD) flow of a visco-elastic, incompressible, and electricity conducting fluid in a medium with porosity is carried out. The novelty of the study is to examine the impact of the visco-elasticity on MHD boundary layer flow, which plays a crucial role in engineering and industrial applications. The model differential equations obtained are in a coupled form which are highly non-linear. The non-dimentional partial differential equations are simplified numerically by employing Crank-Nicolson finite difference scheme. The impact of vital parameters of the flow are discussed and presented graphically. Also, the outcomes of the physical parameters such as skin friction, heat transfer rate, and mass transfer rate are derived and analyzed through tables. It is observed that visco-elastic parameter enhances the velocity profiles in the whole flow region. Also, the velocity gradient growths with the higher value of the visco-elastic parameter and the enhanced value of magnetic parameter diminisheses the profile of velocity.